Desain dan Pengembangan Game Ular Tangga untuk Edukasi Meningkatkan Pengetahuan dan Kepatuhan Konsumsi Tablet Tambah Darah pada Remaja Putri di SMPN 3 Gresik - Permatasari, Riska Dwi; Ariestiningsih, Eka Srirahayu (JGK: Jurnal Gizi dan Kesehatan, 2025)
Anemia is still a major nutritional problem in Indonesia, especially in adolescent girls due to lack of iron intake. One of the efforts to overcome this is by increasing knowledge and compliance in consuming iron tablets (TTD). Education through game media is considered an effective method in conveying health information. Objective: To determine the effect of the design and development of the snakes and ladders educational game on increasing knowledge and compliance in consuming iron tablets in adolescent girls at SMPN 3 Gresik. Method: This study used a quasi-experimental design with a one group pretest–posttest approach. The sample consisted of 36 7th grade female students selected by purposive sampling. The intervention was in the form of educational video screenings and snakes and ladders games. Data were collected using the MMAS-8 questionnaire and analyzed using the paired sample t-test. Results: There was a significant increase between the pretest and posttest results in knowledge and compliance in consuming iron tablets (p <0.05), indicating the effectiveness of the snakes and ladders game media in increasing awareness and compliance in consuming iron tablets. Conclusion: The snakes and ladders educational game has been proven effective in increasing knowledge and compliance in consuming iron tablets in adolescent girls. This media can be used as an alternative method of interesting and interactive nutritional education for the adolescent age group.